Melothria pendula L. (Cucurbitaceae): first report from Java and range extension in Sumatra, Indonesia - Iin Pertiwi A. Husaini; Aulia Hasan Widjaya; Saripudin Saripudin; Ponco Yuliyanto; Dian Latifah; Arifin Surya Dwipa Irsyam; Dian Rosleine; Muhammad Rifqi Hariri (Check List, 2024)
Melothria L. (Cucurbitaceae) is a Neotropical genus of wild cucumber comprising 12 species. The only species that occurs in Malesia is M. pendula L., which has been recorded in Peninsular Malaysia, Borneo, mainland Sumatra, the Philippines, Sulawesi, and Bali. During our botanical excursions in Bangka and West Java from 2020 to 2022, we discovered naturalized populations of M. pendula. Our findings reveal that M. pendula has an extensive distribution in Sumatra and is a newly recorded wild cucumber in Java. We present a morphological description, photographs, and a brief discussion.